Overcoming Obstacles to Peace - Dobbins, James; Miller, Laurel E.; Pezard, Stephanie; Chivvis, Christopher S.; Taylor, Julie E. (RAND Corporation, 2023)
Following on a series of RAND Corporation studies of nation-building, this monograph analyzes the impediments that local conditions pose to successful outcomes in these interventions. It examines how external actors and local leaders in a variety of societies modified or worked around those conditions to promote enduring peace.